ANALISIS PERMASALAHAN PEMBELAJARAN FISIKA PADA SISWA DALAM MEMAHAMI KONSEP DAN RUMUS FISIKA DI SMA KABUPATEN DELI SERDANG - Nia Cristina Simalango; Nora Lidwina Situmorang; Nurul Zahra Sinaga; Nurul Zuriani; Rahmansyah; Selvia Priska Pasaribu (STKIP Subang, 2026)
This study aims to analyze the problems faced by students in understanding physics concepts and formulas at senior high schools in Deli Serdang Regency. The study employed a descriptive qualitative approach, with data collected through interviews with eleventh-grade students. The results showed that students experienced difficulties in memorizing and understanding physics formulas, lacked understanding of basic physics concepts, and had difficulty relating concepts to problem-solving. In addition, the teaching methods used by teachers significantly influenced students' level of understanding. Students found it easier to understand the material when teachers explained concepts in a simple manner, provided examples related to daily life, and applied interactive teaching methods. Therefore, it is necessary to implement learning strategies that focus more on conceptual understanding and utilize engaging and contextual teaching methods to help students better understand physics.